2011
DOI: 10.1785/0120110117
|View full text |Cite
|
Sign up to set email alerts
|

PGA and PGV Spatial Correlation Models Based on European Multievent Datasets

Abstract: Spatial modeling of ground motion intensity measures (IMs) is required for risk assessment of spatially distributed engineering systems. For example, when a lifeline system is of concern, classical site-specific hazard tools, which treat IMs at different locations independently, may not be adequate to accurately assess the seismic risk. In fact, in this case, modeling of ground motion as a random field is required; it basically consists of assigning a correlation structure to the IM of interest. This work focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 27 publications
2
81
0
Order By: Relevance
“…The ground motion prediction equation (GMPE) introduced by Akkar and Bommer (2010) is applied for the estimation of the ground motion parameters on rock. The spatial variability for PGA is modeled using the correlation models provided by Jayaram and Baker (2009) as adapted for European events consistently with the selected GMPE (Esposito and Iervolino, 2011). The primary IM is then retrieved at vulnerable sites by distance-based interpolation and finally the local IM is sampled conditionally on primary IM.…”
Section: Seismic Hazardmentioning
confidence: 99%
“…The ground motion prediction equation (GMPE) introduced by Akkar and Bommer (2010) is applied for the estimation of the ground motion parameters on rock. The spatial variability for PGA is modeled using the correlation models provided by Jayaram and Baker (2009) as adapted for European events consistently with the selected GMPE (Esposito and Iervolino, 2011). The primary IM is then retrieved at vulnerable sites by distance-based interpolation and finally the local IM is sampled conditionally on primary IM.…”
Section: Seismic Hazardmentioning
confidence: 99%
“…Many researchers (e.g. Wang and Takada 2005;Goda and Hong 2008;Jayaram and Baker 2009;Esposito and Iervolino 2011) have shown that the intra-event residuals at two different sites for a given event are correlated, as a function of their separation distance -the greater the distance, the lower the correlation between the residuals. Hence, when modelling distributed ground motions for a future potential scenario earthquake, a sample of the interevent residual/epsilon for the event should be made and then this should be combined (through SRSS) with the intra-event residual/epsilon at each site, which should be obtained by employing a model of spatial correlation of the intra-event residuals (see e.g.…”
Section: Scenario-based Hazard/risk Assessmentmentioning
confidence: 99%
“…Both simulation of PGA and the conditional simulation of PGV are carried out using the GMPE by Akkar and Bommer (2010), recently developed for the European context. Spatial correlation with correlation parameter (range) is estimated based on European records by Esposito et al (2010). For within-site cross-IM correlation ρ PGA,PGV = 0.754 is used.…”
Section: Regional Seismicity Modelmentioning
confidence: 99%